Green Composites Based on Thermoplastic Starch Reinforced with Micro- and Nano-Cellulose by Melt Blending - a Review - Ortiz-Nunez, J; Zapata-Ramirez, P; Cament-Riveros, A; Loyo-Davila, C; Moreno-Serna, V (Elsevier B.V., 2023)
Starch is a biodegradable biopolymer, a sustainable material that can replace conventional petrochemical-based plastics. However, starch has some limitations, as it must be processed by heating and treated mechanically with a plasticizer to become thermoplastic starch (TPS). Different variables such as mixing speeds, amount, and kind of plasticizers play a vital role in preparing TPS by melting. Despite this, the properties of the TPS are not comparable with those of traditional plastics. To overcome this limitation, microcellulose or nanocellulose is added to TPS by melt mixing, including the extrusion and internal mixing process, which enables large-scale production. This review aims to compile several studies that evaluate the effect of plasticizers, as well as the relevance of incorporating different cellulosic fillers of different dimensions on the properties of TPS obtained by melt mixing. Potential applications of these materials in food packaging, biomedical applications, and other opportunities are also described. © 2023 Elsevier B.V.